2019
DOI: 10.1021/acs.orglett.9b00597
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Mediated Decarboxylative Fluorodiiodination of Alkynoic Acids: Synthesis of Regio- and Stereoselective Fluoroalkenes

Abstract: A variety of arylalkynoic acids reacted with 1,3diiodo-5,5-dimethylhydantoin and HF•pyridine in the presence of AgOAc to provide the corresponding 1-fluoro-2,2-diiodovinylarenes in good yields and high regioselectivity. In addition, Pd-catalyzed cross-coupling reaction of 1-fluoro-2,2-diiodovinylarenes afforded diaryl coupling products in the Suzuki reaction and monoaryl coupling products with high stereoselectivity in the Hiyama reaction. It was found that C−Factivated borylation of fluoroalkenes using Pd cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In addition, we have also developed a decarboxylative halogenation reaction of alkynoic acids . Very recently, we reported that 1-fluoro-2,2-diiodovinylarenes can be obtained upon reacting alkynoic acid with Py·HF and 1,3-diiodo-5,5-dimethylhydantoin ( DIH) in the presence of a catalytic amount of AgOAc . 1-Fluoro-2,2-diiodovinylarenes are gem -diiodo-substituted alkenes that can react with a variety of nucleophiles via transition-metal-catalyzed coupling reactions.…”
mentioning
confidence: 99%
“…In addition, we have also developed a decarboxylative halogenation reaction of alkynoic acids . Very recently, we reported that 1-fluoro-2,2-diiodovinylarenes can be obtained upon reacting alkynoic acid with Py·HF and 1,3-diiodo-5,5-dimethylhydantoin ( DIH) in the presence of a catalytic amount of AgOAc . 1-Fluoro-2,2-diiodovinylarenes are gem -diiodo-substituted alkenes that can react with a variety of nucleophiles via transition-metal-catalyzed coupling reactions.…”
mentioning
confidence: 99%
“…Thus, iodophenyl acetylene was prepared from propiolic acid and DIH, in a 91% isolated yield (Scheme 147). 361 Interestingly, when such an iododecarboxylation was performed in the presence of a fluorine source, 2,2-diiodo-1fluoro-alkenes were isolated as the reaction products (Scheme 148a).…”
Section: Halodecarboxylation Of Acetylenic Carboxylic Acidsmentioning
confidence: 99%
“…Following this concept, we successfully obtained 2-fluoro-1,1-diiodoalkenes from the reaction of alkynoic acids with HF•pyridine and 1,3-diiodo-5,5-dimethylhydantoin (DIH) at room temperature in the presence of catalytic AgOAc (Scheme 57). 66 Aryl-and alkyl-substituted propynoic acids provided the desired 2-fluoro-1,1-diiodoalkenes in moderate yields and functional group tolerance. These 2-fluoro-1,1-diiodoalkenes were employed in Pd-catalyzed crosscoupling reactions, such as the Suzuki and Hiyama, and decarboxylative coupling reactions.…”
Section: Fluorodiiodinationmentioning
confidence: 99%